Zum Verhalten von Phorbia phrenione (Séguy) sowie Mitteilungen über Zucht, Neufunde und Feinde der Fliege (Diptera: Anthomyiidae). - Kohlmeyer, Jan; Kohlmeyer, Ernst (Contributions to Entomology = Beiträge zur Entomologie, 1960)
On the behaviour of Phorbia phrenione, on breeding, enemies and new locations of this fly (Diptera: Anthomyiidae). - 1. Observations made in nature and on trapped Phorbia phrenione showed the flies feed on the conidia-bearing stromata of Epichloë typhina before laying eggs on it. Conidia are not digested and may germinate after passing through the digestive tract. P. phrenione may possibly help to distribute the fungus, whose mode of infection of healthy grass-plants is hitherto unknown. - 2. P. phrenione was observed when laying eggs. Four days after egg-deposition the larvae hatched out. - 3. Flies trapped on the stroma of Epichloë were used for experiments on the orientation of the imagines. Besides a stroma of E. typhina a fungus wrapped up with thin cloth and dummies of cloth were offered as choices for sites of egg deposition. It may be concluded from the results that the odour of the fungus is the primary stimulus for laying eggs. The white colour of Epichloë is of minor influence as a stimulus for egg deposition, but it may be important for attracting the flies when they are near by. It seems doubtful that odour has an attracting influence over a long distance. - 4. A method for breeding P. phrenione is described. Besides the imagines of the fly, three species of ichneumon-flies emerged from the pupae of Phorbia. - 5. The following insects were found to be enemies of P. phrenione: Ichneumon-flies as parasites, bugs as robbers, click beetles, chrysomelids, curculionids, ants and loopers as consumers of Epichloë and consequently rivals of the larvae for food, as feeding on the fungal stroma and thus damaging burrows of the larvae. - 6. Sicily has been found to be the southern limit of distribution in Europe. In four localities in this country, flies are reported to have laid their eggs by the beginning of April.